2023
DOI: 10.1177/09612033231170515
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in 1528 Brazilian childhood-onset systemic lupus erythematosus patients

Abstract: Objectives To identify associations between mortality in cSLE patients and their characteristics: clinical and laboratory features, disease activity and damage scores, and treatment; to evaluate risk factors associated with mortality in cSLE; and to determine the most frequent causes of death in this group of patients. Methods We performed a multicenter retrospective cohort using data from 1,528 cSLE patients followed in 27 pediatric rheumatology tertiary centers in Brazil. Patients’ medical records were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…With regard to mortality, a Norway-SLE cohort study showed that SMR was increased to 1.8 (95% CI 1.6-2.2) in incident adult-onset and peaked at 7.2 (95% CI 3.3-14) in cSLE patients [25 cohort [26]. Other common causes of death include infection and vascular disease [2].…”
Section: Systemic Lupus Erythematosus Prognosis and Surveillancementioning
confidence: 99%
“…With regard to mortality, a Norway-SLE cohort study showed that SMR was increased to 1.8 (95% CI 1.6-2.2) in incident adult-onset and peaked at 7.2 (95% CI 3.3-14) in cSLE patients [25 cohort [26]. Other common causes of death include infection and vascular disease [2].…”
Section: Systemic Lupus Erythematosus Prognosis and Surveillancementioning
confidence: 99%